2019
DOI: 10.15395/mkb.v51n1.1479
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-Activated MSC-CM Topical Gel Effective in Increasing PDGF Level, Fibroblast Density, and Wound Healing Process Compared to Subcutaneous Injection Combination

Abstract: Mesenchymal stem cells (MSCs) are multipotent stromal cells that have the capacity to regenerate tissue damage. However, they have several limitations. MSC-CM as a new approach treatment is widely used to solve the limitation of MSC in wound healing. The aim of this study was to evaluate the effectiveness of TNF-α-activated MSC-CM topical gel compare to topical-subcutaneous injection combination on wound healing acceleration. This study was conducted between April-August 2018 at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Therefore, the one primary strategy to accelerate the optimum wound healing without scar formation is by effectively controlling the α-SMA expression using HMSCs treatment. The HMSCs are the most promising therapeutic to control several fibrosis diseases, including scar formation, due to their ability to firmly control the prolonged inflammation for early initiating cell proliferation leading to the optimum wound healing acceleration [23], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the one primary strategy to accelerate the optimum wound healing without scar formation is by effectively controlling the α-SMA expression using HMSCs treatment. The HMSCs are the most promising therapeutic to control several fibrosis diseases, including scar formation, due to their ability to firmly control the prolonged inflammation for early initiating cell proliferation leading to the optimum wound healing acceleration [23], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four wistar rat (four to six-month old, male, body weight 250-300 grams) were obtained from local farmer at the Java Rat Labs, Tembalang, Semarang, Indonesia. The full-thickness wound model was generated as described previously (Kuntardjo, et al, 2019). In brief, after the hair removal from the dorsal surface and anaesthesiae 6-mm full-thickness skin wounds were created on one side of the midline.…”
Section: The Induction Of Full-thickness Wound Modelmentioning
confidence: 99%
“…The full-thickness rats lubricated with different doses of HMSCs-CM in topical gel. The control groups were lubricated with basis of gel, whereas the treatment groups (T1 and T2) received the gel of HMSCs-CM 200 µL and 400 µL, respectively (Kuntardjo, et al, 2019). The gel was applied for control and treatment groups one doses on the day of induction of the full-thickness wound.…”
Section: Hmscs-cm Treatment To Full-thickness Wound Modelmentioning
confidence: 99%
“…7 Preconditioning culture in a hypoxic environment is a procedure to improve the quality of MSCs.3 In wound healing, roles of secretome MSC hypoxia using a topical gel have been shown to be more effective. 8 The effect of giving secretome MSC hypoxia in wound healing requires further research.…”
Section: Introductionmentioning
confidence: 99%
“…12 According to research using topical subcutaneous injection of MSC-CM, compared with topical gel MSC-CM worked better on day 6, it was found that the topical group had significantly higher levels of PDGF and fibroblast density on day 6 of wound healing. 8 MSCs can also reduce inflammation, and burn scar formation, and have been shown in preclinical trials to accelerate the healing of acute burn wounds. 13 Other studies at TNF-α concentrations of 5 and 10 ng/mL significantly increased TGF-β and IL-10 levels.…”
Section: Introductionmentioning
confidence: 99%